The Effect of Onboarding Employees on Talent Retention: A field research in a Sample of Iraqi Private Banks - Adel Manhal *, Hassan; Dahham Al.zubaidi , Ghani (Journal of Economics and Administrative Sciences, 2024)
The purpose of this research is to understand the nature of the relationship and the level of impact between employee onboarding and talent retention. Employee onboarding assists employees adapting the social aspects of the organization and their new roles more easily, thereby increasing their productivity, satisfaction, and loyalty. The research also aims to identify the factors that encourage employees to stay with the organization. The research problem is highlighted by a talent shortage and the difficulty of identifying the factors that facilitate the integration of employees into the workplace and their retention within the organization. Moreover, it seeks to determine the extent to employee onboarding as one of the essential requirements for organizations, affects talent retention and prevented loss them. the research was conducted in 12 private banks in Iraq, with a total of 147 respondents from employees in the upper and middle-level management positions. The primary data collection tool is a questionnaire. Data analysis and hypothesis testing were conducted using various computer software programs such as (SPSS V. 26) and (Amos V. 26). The results of the research indicate a significant impact of employee onboarding on talent retention.